The exporter and productivity dynamics: The effect of trade liberalization - Kazuma Inagaki (Osaka University, Institute of Social and Economic Research (ISER), 2024)
This paper studies how investment in R&D and export technology amplifies the welfare gains from trade liberalization. I develop a dynamic heterogeneous firm international trade model with investment in productivity-enhancing R&D and export technology. I find that R&D investment combined with a dynamic export technology enhances the welfare gains from trade liberalization. I quantitatively demonstrate that the welfare gain from trade liberalization in the dynamic trade model with elastic R&D is above 30% higher than that with inelastic R&D. By contrast, in a static trade model, the elasticity of R&D has a small impact on welfare gain. These findings suggest that static trade models may provide an even poorer approximation of dynamic trade models than we thought.
Keywords: F1; F4; O3; 330; Trade liberalization; Firm dynamics; Heterogeneous firms; Innovation